Can Social Capital Play a Role in the Impact of Tax Complexity on Tax Compliance? - Ari Budi Kristanto (Bongaya Journal for Research in Accounting (BJRA), 2021)
This study aims to examine the effect of tax complexity based on taxes and test the moderating effect of social capital. This study uses secondary data in the form of the Tax Complexity Index report, the results of the research on the level of tax effort, and the State Prosperity Index. The population in this study are countries around the world, with a sample of 84 countries. This research is a quantitative study using the Medium Regression Analysis test. The results of this study indicate that tax complexity does not affect tax comments. However, when taxes are accounted for with complexity, it appears that the tax is becoming stronger. Based on the research results, the government is expected to take advantage of substantial social capital to focus on designing tax policies that can encourage people to exemplify each other to comply with taxes.